Ecological and economic aspects of changing the land`s legal status for the needs of road transport - Stetsyuk, M.; Ischenko, N. (Land Management, Cadastre and Land Monitoring, 2019)
An analysis of the land transport structure which are owned or used by enterprises and organizations in the composition of land has been determined. Ukraine transport lands have been formed by ownership type. It was clarified that change in the purposeful use of land plots which are in state or communal property is carried out by executive authorities or local self-government bodies, which make decisions on approval of land utilization projects for the allocation of land plots and the transfer of these plots into ownership or provision for use in accordance with the Land Code of Ukraine. Changing the legal status for the needs of land road transport the policy and main priorities should be aimed at the creation and operation of such rules and standards that reflect both public interests and the interests of landowners and land users as well as European requirements, since in recent years transport infrastructure has evolved towards the European integration. The main interests should be environmental interests in ensuring the reduction of atmospheric air pollution by emissions of motor vehicles, the removal of agricultural and forest land for public use. Economic interests should ensure the construction of toll-free highways of the European format The implementation of ecological and economic instruments is proposed, namely: instruments of economic guaranteeing, innovative and investment instruments of land relations development. Key words: categories of lands, ecological-economic aspects, roads of motor transport, change of legal status.